METHODS FOR CALCULATION OF COMPENSATION FOR EXPROPRIATION OF A FOREIGN INVESTMENT - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
A legal expropriation of a foreign investment without exception includes an obligation of the host state to pay the investor an appropriate compensation for the taking. Bilateral treaties for protection and encouragement of investments which usually serve as a normative basis for arbitration of expropriation disputes contain provisions instructing contracting states to provide “adequate”, “just” compensation or to pay the compensation in “full” or “genuine” value of the expropriated investment etc. However, the sole existence of the standard for payment of compensation is not by itself enough for establishing the precise sum of compensation in particular cases. This purpose is served by mathematical methods of calculation employed used in judicial and arbitral practice. The paper contains an overview of the most important methods for calculation in practice: the market value method, the discounted cash flow method and the book value method. It also identifies the differences between situations in which different methods are used and explains how the nature of an investment and circumstances of particular case affect the choice of a particular method by the arbitral tribunal.